The influence of the career calling on the employees’ creative deviance - Liu, Xiwei; Xu, Yunbao (Frontiers in Psychology, 2022)
As creative deviance can improve organizational innovation ability and competitiveness effectively, scholars have recently paid much attention to this innovative manner. This paper examines the mechanism between career calling and creative deviance based on 304 surveyed samples via a cross-temporal questionnaire. The results show that employees’ career calling exerts a significant positive impact on their creative deviance, and employee creativity plays a mediating role in this relationship. Furthermore, ethical leadership positively moderates the relationship between career calling and employee creativity as well as the relationship between career calling and creative deviance.